Naphthenic base oil hydroisomerization catalyst and method for making same

CN122937846APending Publication Date: 2026-10-20SHAANXI COAL-BASED SPECIAL FUEL RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611246038.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]有鉴于此,本发明提供了环烷基油临氢异构反应催化剂及其制备方法,用以解决现有技术中环烷基油临氢异构催化剂活性组分分散稳定性不足且异构化选择性与液体产品收率难以兼顾的问题

Benefits of technology

本发明实施例提供的环烷基油临氢异构反应催化剂及其制备方法,复合载体由分子筛、无机氧化物粘结剂和成型助剂制得,能够为临氢异构反应提供适宜的酸性反应环境和稳定的载体结构;活性组分体系包括铂和锡,铂组分提供加氢/脱氢活性中心,促进正构烷烃异构化反应的进行,锡组分对铂组分进行改性,有利于提高活性组分的分散稳定性;同时,活性组分体系经卤代脂肪酸类分散剂分散改性形成,使活性组分能够更加均匀地分布于复合载体表面及孔道内部,降低活性组分迁移和团聚的发生概率。通过复合载体、铂组分、锡组分以及卤代脂肪酸类分散剂之间的协同作用,在提高活性组分分散稳定性的同时,有效调控异构化反应与裂解反应之间的平衡关系,促进原料向目标异构烷烃转化,抑制深度裂解副反应,从而提高异构化选择性和液体产品收率,解决了现有技术中环烷基油临氢异构催化剂易发生活性组分团聚和裂解副反应,导致异构化选择性与液体产品收率难以兼顾的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of hydrogenation catalysis technology, addressing the problems of insufficient dispersion stability of active components and difficulty in simultaneously achieving isomerization selectivity and liquid product yield in existing cycloalkyl oil hydroisomerization catalysts. It provides a cycloalkyl oil hydroisomerization catalyst and its preparation method. The cycloalkyl oil hydroisomerization catalyst comprises a composite support and an active component system supported on the composite support. The composite support is prepared from composite support raw materials, including molecular sieves, inorganic oxide binders, and molding aids. The active component system comprises noble metal components and metal-modifying aids, and is formed by dispersion modification with halogenated fatty acid dispersants. This invention improves the dispersion stability and isomerization selectivity of the active components, increasing liquid product yield while lowering the product pour point.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogenation catalysis, and more particularly to a catalyst for the hydroisomerization reaction of cycloalkyl oils and its preparation method. Background Technology

[0002] Transformer oil is a crucial insulating and heat dissipation medium in the operation of power equipment. Its low-temperature fluidity, oxidation stability, and electrical insulation properties directly affect the operational safety and service life of power equipment. Naphthenic oils, due to their excellent electrical properties and oxidation stability, are widely used as base oils for high-quality transformer oils. However, naphthenic oils typically contain a certain proportion of n-chain long-chain alkanes. These components have high pour points and can easily lead to a decrease in the low-temperature fluidity of the oil. Therefore, a hydroisomerization pour point reduction process is needed to convert n-chain alkanes into branched isoalkanes to lower the pour point and improve the low-temperature performance of the oil.

[0003] Currently, the catalysts used in the hydroisomerization and pour point depletion process of naphthenic oils typically employ molecular sieves as supports, loaded with noble metal active components. The hydroisomerization reaction is achieved through the synergistic effect of the metal active centers and the acidic centers of the molecular sieve. However, existing catalysts still have the following shortcomings: Firstly, the noble metal components are prone to migration and aggregation during catalyst preparation and use, leading to decreased metal dispersion and reduced catalytic activity. Secondly, the strong acid centers on the surface of the molecular sieve support easily induce deep cracking reactions in the feedstock, converting some feedstock into light hydrocarbon byproducts and reducing the yield of the target product. Furthermore, existing catalysts struggle to balance isomerization activity, isomerization selectivity, and liquid product yield, thus limiting the overall performance improvement of the resulting naphthenic transformer oil.

[0004] Chinese patent CN114806634A discloses a transformer oil base oil and its preparation method. This method involves sequentially hydrorefining, hydrodewaxing, supplemental hydrorefining, and fractionation of a naphthenic oil fraction. The resulting first component is then mixed with a second component obtained through isomerization dewaxing at a predetermined ratio to obtain a transformer oil base oil with a low pour point, low low-temperature kinematic viscosity, and good oxidation stability. The noble metal catalyst used for isomerization dewaxing includes SAPO-11 molecular sieve, ZSM-22 molecular sieve, and a platinum active metal component, which undergoes hydrogen reduction pretreatment before use. While this patent can improve the overall performance of transformer oil through the selection of raw material fractions, segmented processing, and blending of different base oil components, its technical focus is mainly on the preparation route and blending ratio of the transformer oil components. It does not propose a specific method for controlling the dispersion stability of the platinum active component on the composite molecular sieve support, nor does it address the synergistic inhibition of noble metal migration and agglomeration using metal-modifying additives and specific dispersants. Therefore, under long-term reaction conditions, there may still be problems such as uneven distribution of precious metal particles and decreased utilization of metal active centers.

[0005] Chinese patent CN110540873A discloses a method for processing naphthenic oils. This method employs a tandem hydrogenation process combining hydrotreating, hydrodewaxing, and deep refining to produce naphthenic specialty oils. The hydrodewaxing catalyst contains ZSM-5 molecular sieves and nickel or cobalt active components; the hydrorefining catalyst uses platinum and / or palladium as the hydrogenation component and employs small-crystal Y-type molecular sieves, amorphous silica-alumina, and alumina as the catalyst support. While this patent achieves hydrotreating, dewaxing, and refining of naphthenic oils through the combination of different reaction zones and catalysts, its hydrodewaxing catalyst uses non-precious metal active components, with precious metal catalysts primarily used for subsequent refining reactions. It does not form a precious metal-modified metal composite active system for the hydroisomerization reaction of naphthenic oils. Furthermore, this patent does not address controlling the distribution of active components on the surface and within the pores of the molecular sieve using specific dispersants, thus making it difficult to simultaneously address isomerization and cracking reactions from the perspective of the dispersion state of the catalyst active components.

[0006] Therefore, how to improve the dispersion stability of active components in cycloalkyl oil hydroisomerization catalysts, and suppress cracking side reactions while improving isomerization selectivity, thereby balancing low pour point performance and liquid product yield, is an urgent technical problem to be solved. Summary of the Invention

[0007] In view of this, the present invention provides a cycloalkyl oil hydroisomerization catalyst and its preparation method, in order to solve the problems of insufficient dispersion stability of active components and difficulty in achieving both isomerization selectivity and liquid product yield in the prior art of cycloalkyl oil hydroisomerization catalysts.

[0008] In a first aspect, embodiments of the present invention provide a catalyst for the hydroisomerization reaction of cycloalkyl oil, comprising a composite support and an active component system supported on the composite support; The composite carrier is prepared by mixing, molding and calcining composite carrier raw materials, which include molecular sieves, inorganic oxide binders and molding aids. The active component system is a Pt-Sn bimetallic composite system, which includes a noble metal component and a metal-modifying agent, and the active component system is formed by dispersion modification with a halogenated fatty acid dispersant.

[0009] Preferably, the molecular sieve includes two of ZSM-23, ZSM-48 and ZSM-22, and the molecular sieve accounts for 20-80% of the total mass of the composite carrier raw material.

[0010] Preferably, the inorganic oxide binder includes γ-alumina, and the γ-alumina accounts for 10-30% of the total mass of the composite carrier raw materials.

[0011] Preferably, the molding aid includes guar gum powder, which accounts for 2-5% of the total mass of the composite carrier raw materials.

[0012] Preferably, the platinum accounts for 0.3-1% of the total mass of the catalyst.

[0013] Preferably, the tin accounts for 1.5-5% of the total mass of the catalyst.

[0014] Preferably, the halogenated fatty acid dispersant includes monochloroacetic acid, dichloroacetic acid, monobromoacetic acid, and dibromoacetic acid; the halogenated fatty acid dispersant accounts for 0.5-2% of the total mass of the catalyst.

[0015] In a second aspect, embodiments of the present invention provide a method for preparing a cycloalkyl oil hydroisomerization catalyst, used to prepare the cycloalkyl oil hydroisomerization catalyst as described in the first aspect, the method comprising: The molecular sieve, the inorganic oxide binder, and the molding aid are mixed evenly, and then an acidic solution of a preset concentration is added and kneaded to obtain a plastic mixture. The plastic mixture is extruded, dried, and calcined to obtain a composite carrier; The first amount of platinum-containing precursor impregnation solution is determined based on the water absorption rate of the composite carrier. According to the first dosage, the platinum-containing precursor impregnation liquid is loaded onto the composite support using a negative pressure equal volume impregnation method, and the loaded composite support is dried and calcined to obtain a platinum-loaded catalyst precursor. The second amount of the secondary impregnation solution is determined based on the water absorption rate of the catalyst precursor. According to the second dosage, the tin-containing precursor solution is mixed with the halo-fatty acid dispersant solution to obtain the secondary impregnation solution. The secondary impregnation solution is loaded onto the catalyst precursor by an equal-volume impregnation method, and the loaded catalyst precursor is dried and calcined to obtain the catalyst semi-finished product. The catalyst semi-finished product was reduced under a hydrogen atmosphere to obtain the cycloalkyl oil hydroisomerization catalyst.

[0016] Preferably, the step of loading the platinum-containing precursor impregnation solution onto the composite support using a negative pressure equal-volume impregnation method according to the first dosage, and then drying and calcining the loaded composite support to obtain the platinum-supported catalyst precursor includes: Chloroplatinic acid was dissolved in deionized water to prepare a platinum-containing precursor impregnation solution. The composite carrier is placed under negative pressure and vacuumed to remove the gas from the pores of the composite carrier. The platinum-containing precursor impregnation solution is introduced into the composite carrier according to the first dosage, so that the platinum-containing precursor impregnation solution enters the pores of the composite carrier under negative pressure and completes the equal volume impregnation. The impregnated composite carrier is dried at 90-120℃ for 12-36 hours. The dried composite support was calcined at 500-650℃ for 1-4 hours to obtain the catalyst precursor.

[0017] Preferably, the second impregnation solution is obtained by mixing the tin-containing precursor solution with the halofatty acid dispersant solution according to the second dosage. The secondary impregnation solution is then loaded onto the catalyst precursor using an equal-volume impregnation method. The loaded catalyst precursor is then dried and calcined to obtain a catalyst semi-finished product comprising: The halogenated fatty acid dispersant is dissolved in a solvent to obtain a halogenated fatty acid dispersant solution. Tin chloride was dissolved in ethanol to obtain a tin-containing precursor solution; The tin-containing precursor solution is added to the halo-fatty acid dispersant solution according to the second dosage and mixed to obtain the secondary impregnation solution; The secondary impregnation solution is loaded onto the surface and pores of the catalyst precursor using an equal-volume impregnation method, so that the tin component and the halogenated fatty acid dispersant are uniformly dispersed on the catalyst precursor. The impregnated catalyst precursor was dried at 90-120℃ for 12-36 hours. The dried catalyst precursor was calcined at 500-650℃ for 1-4 hours to obtain the catalyst semi-finished product.

[0018] In summary, the beneficial effects of the present invention are as follows: The cycloalkyl oil hydroisomerization catalyst and its preparation method provided in this invention have a composite support made of molecular sieves, inorganic oxide binders, and molding aids, which can provide a suitable acidic reaction environment and a stable support structure for the hydroisomerization reaction. The active component system includes platinum and tin. The platinum component provides hydrogenation / dehydrogenation active centers to promote the isomerization reaction of n-alkanes, and the tin component modifies the platinum component, which is beneficial to improving the dispersion stability of the active component. At the same time, the active component system is formed by dispersion modification with halogenated fatty acid dispersants, so that the active component can be more uniformly distributed on the surface and inside the pores of the composite support, reducing the probability of migration and agglomeration of the active component. Through the synergistic effect of the composite support, platinum component, tin component, and halogenated fatty acid dispersant, the dispersion stability of the active component is improved while effectively regulating the balance between isomerization and cracking reactions. This promotes the conversion of raw materials to target isomeric alkanes and inhibits deep cracking side reactions, thereby improving isomerization selectivity and liquid product yield. This solves the problem in the existing technology where cycloalkyl oil hydroisomerization catalysts are prone to active component agglomeration and cracking side reactions, making it difficult to achieve both isomerization selectivity and liquid product yield. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the embodiments of the present invention will be briefly introduced below. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, and these are all within the protection scope of the present invention.

[0020] Figure 1 This is a schematic flowchart of the method for preparing the catalyst for the hydroisomerization reaction of cycloalkyl oil in the embodiments of the present invention; Figure 2 This is a comparison diagram of the metal dispersion of catalysts in various embodiments and comparative examples of the present invention; Figure 3 This is a comparison diagram of the pour points of oils treated with catalysts in various embodiments and comparative examples of the present invention; Figure 4 This is a density comparison diagram of the oil products after catalyst treatment in various embodiments and comparative examples of the present invention; Figure 5 This is a comparison chart of the liquid absorption rates of the catalysts in various embodiments and comparative examples of the present invention. Detailed Implementation

[0021] The features and exemplary embodiments of various aspects of the present invention will now be described in detail. To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be practiced without some of these specific details. The following description of the embodiments is merely intended to provide a better understanding of the present invention by illustrating examples of the invention.

[0022] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes said element.

[0023] It should be noted that all actions involving the acquisition of signals, information, or data in this invention are carried out in compliance with the relevant data protection laws and regulations of the locality and with authorization from the owner of the relevant device.

[0024] This invention provides a catalyst for the hydroisomerization reaction of cycloalkyl oils, comprising a composite support and an active component system supported on the composite support; The composite carrier is prepared by mixing, extruding and calcining composite carrier raw materials, which include molecular sieves, inorganic oxide binders and molding aids. The active component system is a Pt-Sn bimetallic composite system, which includes a noble metal component and a metal-modifying agent. The active component system is formed by in-situ dispersion modification with a halogenated fatty acid dispersant.

[0025] Specifically, the cycloalkyl oil hydroisomerization catalyst is composed of a composite support and an active component system. The composite support is the main structure that carries the active component and provides the reaction environment. Molecular sieves, as the core functional component of the composite support, have a regular pore structure and acidic centers, which can provide isomerization reaction sites for the conversion of n-alkanes to isoalkanes. Inorganic oxide binders are used to connect molecular sieve particles to form an integral structure with certain mechanical strength and stability, while improving the catalyst's molding performance and wear resistance. Molding aids are used to improve the plasticity of the support during kneading and molding processes, so that the resulting composite support has a more uniform pore structure and a suitable specific surface area.

[0026] The active component system is loaded onto the surface and internal pores of the composite support. Platinum, a noble metal, provides active centers for hydrogenation and dehydrogenation, promoting the dehydrogenation activation of alkane molecules and subsequent hydrogenation stabilization during the hydroisomerization reaction, thereby improving the efficiency of the isomerization reaction. Tin, as a metal modifier, works synergistically with the platinum component to regulate its electronic state and spatial distribution, reducing the migration tendency of platinum particles during preparation and reaction. Simultaneously, a halofatty acid dispersant is introduced during the formation of the active component system for dispersion modification. This dispersant interacts with the metal precursor during the active component loading stage, resulting in more uniform dispersion of platinum and tin components on the surface and within the pores of the composite support, reducing local enrichment of active components and lowering the possibility of agglomeration during subsequent calcination and reaction. Through the synergistic effect of the acidic centers of molecular sieves, the active centers of hydrogenation and dehydrogenation of platinum components, the modification effect of tin components, and the dispersing effect of halogenated fatty acid dispersants, the conversion of normal long-chain alkanes to branched isoalkanes is promoted while inhibiting the occurrence of deep cracking reactions, thereby improving isomerization selectivity and liquid product yield, achieving a balance between low pour point and high liquid yield.

[0027] Preferably, the molecular sieve includes two of ZSM-23, ZSM-48 and ZSM-22, and the molecular sieve accounts for 20-80% of the total mass of the composite carrier raw material.

[0028] Specifically, molecular sieves are key components in composite supports, providing acidic centers and pore structures for isomerization reactions. ZSM-23, ZSM-48, and ZSM-22 are all mesoporous molecular sieves, each with different pore sizes, morphologies, and acidity distribution characteristics. ZSM-22 and ZSM-23 possess one-dimensional pore structures, exhibiting strong shape-selective effects on straight-chain alkanes, thus promoting the conversion of n-alkanes to single- or multi-branched isoalkanes. ZSM-48 has a more unique pore structure and acidity characteristics, reducing the tendency for deep cracking while maintaining isomerization activity. Therefore, selecting two molecular sieves from ZSM-23, ZSM-48, and ZSM-22 for blending allows the pore structure and acidity characteristics of different molecular sieves to complement each other.

[0029] Based on the pour point requirements, liquid yield requirements, and feedstock composition of the target product, the ratio of two target molecular sieves was determined, and they were then mixed with inorganic oxide binders and molding aids to prepare a composite support. The compounded molecular sieve system not only constructs a richer pore network structure, increasing the probability of feedstock molecules entering active sites, but also regulates the balance between isomerization and cracking reactions through the synergistic effect of different acidic centers. Controlling the molecular sieve content at 20-80% of the total mass of the composite support feedstock ensures that the composite support has a sufficient number of acidic active centers, thus maintaining high isomerization activity; on the other hand, it avoids the problems of decreased mechanical strength, poor pore structure stability, and increased cracking side reactions caused by excessively high molecular sieve content. When the molecular sieve content and inorganic oxide binder form a reasonable ratio, the composite support simultaneously possesses good structural stability, suitable acid strength, and high isomerization selectivity, which is beneficial for promoting the conversion of n-chain alkanes in cycloalkyl oils to target isoalkanes, lowering the product pour point, and improving liquid product yield and long-term catalyst stability.

[0030] Preferably, the inorganic oxide binder includes γ-alumina, and the γ-alumina accounts for 10-30% of the total mass of the composite carrier raw materials.

[0031] Specifically, inorganic oxide binders are used to bind molecular sieve particles to form a composite support with certain mechanical strength and structural stability. Among these, γ-alumina, an inorganic oxide material with a high specific surface area and abundant pore structure, not only serves as a support framework to improve the catalyst's formability and compressive strength but also provides more attachment sites for the loading of active components. Simultaneously, γ-alumina itself possesses a well-developed mesoporous structure, which improves the connectivity of pores within the composite support, allowing raw material molecules and hydrogen to diffuse more easily into the active regions inside the molecular sieve and promoting the timely diffusion of reaction products away from the catalyst surface, thereby reducing the impact of diffusion resistance on reaction efficiency. Furthermore, γ-alumina can regulate the overall acidity distribution of the composite support, preventing excessive concentration of acidic centers in the molecular sieve that could trigger overly strong cracking reactions, thus improving the selectivity of the isomerization reaction.

[0032] Controlling the γ-alumina content to 10-30% of the total mass of the composite support raw materials ensures both the catalyst's mechanical strength and formability while maintaining a high proportion of the molecular sieve active components. When the γ-alumina content is below this range, the support strength is insufficient, making it prone to breakage during preparation and use. Conversely, excessively high γ-alumina content dilutes the number of active sites in the molecular sieve, reducing the catalyst's isomerization activity. Therefore, by controlling the γ-alumina content within the aforementioned range, the composite support can possess excellent mechanical stability, pore structure characteristics, and acidity control capabilities, providing a stable support foundation for the uniform loading of platinum and tin components. This, in turn, is beneficial for improving the isomerization efficiency, liquid product yield, and catalyst lifespan during the hydroisomerization reaction of cycloalkyl oils.

[0033] Preferably, the molding aid includes guar gum powder, which accounts for 2-5% of the total mass of the composite carrier raw materials.

[0034] Specifically, molding aids are used to improve the plasticity, adhesion, and molding stability of composite carriers during preparation. Guaranteed guar powder is a commonly used organic molding aid in catalyst carrier molding processes. It possesses excellent water absorption and swelling properties, as well as good adhesion properties. During mixing, it can adsorb and retain an appropriate amount of moisture, allowing molecular sieves and γ-alumina particles to form a uniform and stable plastic system. Controlling the guaranteed guar powder content to 2-5% of the total mass of the composite carrier raw materials ensures both molding performance and carrier structural stability.

[0035] Preferably, the platinum accounts for 0.3-1% of the total mass of the catalyst.

[0036] Preferably, the tin accounts for 1.5-5% of the total mass of the catalyst.

[0037] Preferably, the halogenated fatty acid dispersant includes monochloroacetic acid, dichloroacetic acid, monobromoacetic acid, and dibromoacetic acid; the halogenated fatty acid dispersant accounts for 0.5-2% of the total mass of the catalyst.

[0038] Specifically, platinum, as a noble metal component in the active component system, is one of the core components for the catalyst to exert its activity in the hydroisomerization reaction. Platinum has excellent hydrogenation and dehydrogenation catalytic capabilities. During the reaction, it can promote the dehydrogenation activation of n-alkane molecules, transforming them into intermediates that are more prone to skeletal rearrangement. Simultaneously, it can promptly hydrogenate and stabilize the intermediates after the isomerization reaction, thereby improving the isomerization reaction efficiency and reducing side reactions. Since platinum is a noble metal, its activity is closely related to its dispersion state. When platinum is loaded in a highly dispersed form on the surface and inside the pores of the composite support, more usable active sites can be formed, improving the utilization efficiency per unit mass of platinum. Controlling the platinum content at 0.3-1% of the total catalyst mass ensures sufficient hydrogenation and dehydrogenation activity while balancing economy and catalyst stability. When the platinum content is below this range, the number of active centers in the catalyst is insufficient, making it difficult to effectively promote the isomerization reaction; while when the platinum content is too high, it easily increases the contact probability between platinum particles, leading to agglomeration of the active component, which not only reduces metal dispersion but also increases the catalyst preparation cost.

[0039] Tin, as a metal modifier, is mainly used to regulate the dispersion state of platinum components and the reaction characteristics of catalyst surfaces. During the loading of active components, tin can form a synergistic distribution structure with platinum, regulating the electronic environment and spatial distribution of platinum components, thereby reducing the migration ability of platinum particles during calcination and reaction, and improving the dispersion stability of platinum components. Simultaneously, the introduction of tin can also regulate the reaction pathways on the catalyst surface, reducing the tendency for deep cracking reactions induced by some strongly acidic sites, and allowing more raw materials to be converted towards isomerization. In specific implementation, by controlling the loading amount of tin, it is ensured to be uniformly distributed on the surface and inside the pores of the composite support, forming a stable synergistic system with the platinum components. Controlling the tin content at 1.5-5% of the total catalyst mass can improve platinum dispersion and stability while avoiding excessive tin covering active sites. When the tin content is too low, the modification effect on the platinum components is limited, making it difficult to fully exert the role of stabilizing active components and regulating reaction selectivity; while when the tin content is too high, it may shield some platinum active sites, affecting the overall activity of the catalyst.

[0040] Halogenated fatty acid dispersants are used to modify the dispersion of active component systems. Monochloroacetic acid, dichloroacetic acid, monobromoacetic acid, and dibromoacetic acid are all organic acid compounds containing halogen substituents, possessing both the coordination ability of organic acids and the unique electronic effects of halogen groups. During the preparation of active components, halogenated fatty acid dispersants can interact with metal precursors, resulting in a more uniform dispersion of platinum and tin components during the impregnation stage. They also promote the migration and distribution of metal components into the pores of the composite support, thereby reducing local enrichment. With subsequent calcination and reduction processes, the dispersion-modified active component system maintains high metal dispersion, reducing the possibility of particle growth and agglomeration, and improving the exposure and utilization efficiency of active sites. Controlling the content of halogenated fatty acid dispersants at 0.5-2% of the total catalyst mass maximizes their dispersive modification effect on the active components. Below this range, the improvement effect on metal component dispersion is not significant; above this range, it may affect the normal loading of active components and subsequent catalytic performance.

[0041] Please see Figure 1 This invention provides a method for preparing a cycloalkyl oil hydroisomerization catalyst, the method comprising: The molecular sieve, the inorganic oxide binder, and the molding aid are mixed evenly, and then an acidic solution of a preset concentration is added and kneaded to obtain a plastic mixture. The plastic mixture is extruded, dried, and calcined to obtain a composite carrier; Specifically, the molecular sieve, γ-Al₂O₃, and guar gum powder are first thoroughly mixed in a kneader. The molecular sieve, as the main acidic functional component in the isomerization reaction, provides acidic active centers for the subsequent isomerization of n-alkane skeletons. γ-Al₂O₃, as an inorganic oxide binder, not only improves the mechanical strength of the carrier but also provides a certain mesoporous structure, improving molecular diffusion performance. Guar gum powder, as an organic molding aid, improves the plasticity and extrusion properties of the mixture. Subsequently, a 1%-3% (w / w) dilute nitric acid solution is prepared and slowly and uniformly added during continuous kneading. The dilute nitric acid provides adequate moisture to the kneading system, ensuring thorough wetting of the components and forming a uniform slurry. It also moderately acidifies the surface of γ-Al₂O₃, improving its dispersibility and binding ability, resulting in a more stable bond between the molecular sieve and alumina. As the kneading process continues, the components gradually form a uniform plastic body, which is then extruded through an extruder to form a strip-shaped carrier. The extruded sample was dried at 90-120℃ for 12 hours to gradually remove free water and some bound water from the system, avoiding cracking of the carrier due to rapid evaporation of moisture during subsequent high-temperature calcination. Then, it was calcined at 500-600℃ for 1-5 hours, during which the guar gum powder decomposed and burned off under high temperature, forming a large number of micropores and mesopores inside the carrier. At the same time, the γ-Al2O3 framework was further stabilized, and finally a composite carrier with high specific surface area, suitable pore volume and good mechanical strength was obtained.

[0042] The first amount of platinum-containing precursor impregnation solution is determined based on the water absorption rate of the composite carrier. Specifically, the water absorption rate of the composite support needs to be measured before loading the platinum component. Since the pore volume and pore structure of different batches of supports may vary, directly using a fixed volume of impregnation solution for loading can easily lead to insufficient or excessive impregnation, thus affecting the uniformity of the active component distribution. Therefore, the actual water absorption rate of the support is obtained by measuring the volume of liquid that a unit mass of composite support can absorb, and this is used to calculate the initial amount of chloroplatinic acid impregnation solution. When the volume of the impregnation solution is approximately the same as the pore volume of the support, the impregnation solution can precisely fill the internal pores of the support without generating a large amount of residual liquid, thus achieving true equal-volume impregnation. This not only prevents the accumulation of precious metal precursors on the outer surface of the support but also allows the platinum component to penetrate deep into the pores of the support, improving the uniformity of the active component distribution and the metal utilization rate.

[0043] According to the first dosage, the platinum-containing precursor impregnation liquid is loaded onto the composite support using a negative pressure equal volume impregnation method, and the loaded composite support is dried and calcined to obtain a platinum-loaded catalyst precursor. Preferably, the step of loading the platinum-containing precursor impregnation solution onto the composite support using a negative pressure equal-volume impregnation method according to the first dosage, and then drying and calcining the loaded composite support to obtain the platinum-supported catalyst precursor includes: Chloroplatinic acid was dissolved in deionized water to prepare a platinum-containing precursor impregnation solution. The composite carrier is placed under negative pressure and vacuumed to remove the gas from the pores of the composite carrier. The platinum-containing precursor impregnation solution is introduced into the composite carrier according to the first dosage, so that the platinum-containing precursor impregnation solution enters the pores of the composite carrier under negative pressure and completes the equal volume impregnation. The impregnated composite carrier is dried at 90-120℃ for 12-36 hours. The dried composite support was calcined at 500-650℃ for 1-4 hours to obtain the catalyst precursor.

[0044] Specifically, after determining the amount of chloroplatinic acid impregnation solution, the composite carrier is placed in a negative pressure environment for impregnation treatment. The core of negative pressure equal-volume impregnation lies in utilizing the pressure difference to enhance the ability of the impregnation solution to penetrate into the pores of the carrier. In traditional atmospheric pressure impregnation, residual air inside some micropores can easily hinder the entry of the impregnation solution. However, negative pressure treatment can remove the air in the pores beforehand, allowing the chloroplatinic acid solution to rapidly enter the deep pores of the carrier under the drive of the pressure difference, achieving a uniform distribution from the outer surface to the internal pore structure. After impregnation, drying is carried out at 90-120℃ for 12-36 hours to allow the solvent to evaporate slowly and avoid redistribution of the metal precursor due to liquid migration. Subsequently, calcination is carried out at 500-650℃ for 1-4 hours. During calcination, chloroplatinic acid gradually decomposes into stable platinum active species, which firmly adhere to the surface and pore structure of the carrier, while further stabilizing the carrier structure.

[0045] The second amount of the secondary impregnation solution is determined based on the water absorption rate of the catalyst precursor. According to the second dosage, the tin-containing precursor solution is mixed with the halo-fatty acid dispersant solution to obtain the secondary impregnation solution. The secondary impregnation solution is loaded onto the catalyst precursor by an equal-volume impregnation method, and the loaded catalyst precursor is dried and calcined to obtain the catalyst semi-finished product. Preferably, the second impregnation solution is obtained by mixing the tin-containing precursor solution with the halofatty acid dispersant solution according to the second dosage. The secondary impregnation solution is then loaded onto the catalyst precursor using an equal-volume impregnation method. The loaded catalyst precursor is then dried and calcined to obtain a catalyst semi-finished product comprising: The halogenated fatty acid dispersant is dissolved in a solvent to obtain a halogenated fatty acid dispersant solution. Tin chloride was dissolved in ethanol to obtain a tin-containing precursor solution; The tin-containing precursor solution is added to the halo-fatty acid dispersant solution according to the second dosage and mixed to obtain the secondary impregnation solution; The secondary impregnation solution is loaded onto the surface and pores of the catalyst precursor using an equal-volume impregnation method, so that the tin component and the halogenated fatty acid dispersant are uniformly dispersed on the catalyst precursor. The impregnated catalyst precursor was dried at 90-120℃ for 12-36 hours. The dried catalyst precursor was calcined at 500-650℃ for 1-4 hours to obtain the catalyst semi-finished product.

[0046] Specifically, since the pore structure of the catalyst precursor has changed to some extent after the first impregnation, the water absorption rate of the catalyst precursor is first measured, and the second amount of the second impregnation liquid is calculated based on the measured water absorption rate so that the volume of the subsequent impregnation liquid matches the pore volume of the catalyst precursor, thereby ensuring that the active components can uniformly enter the internal pores of the support during the second impregnation process.

[0047] In the specific implementation process, firstly, halogenated fatty acid dispersants such as monochloroacetic acid, dichloroacetic acid, monobromoacetic acid, or dibromoacetic acid are added to the solvent and fully dissolved to form a homogeneous and stable dispersant solution; simultaneously, tin chloride is dissolved in ethanol solvent to obtain a tin-containing precursor solution with a concentration of 0.2 g / L. Ethanol is used as the solvent for tin chloride because it can improve the dispersion uniformity of tin chloride and reduce the local aggregation of metal ions in the solution.

[0048] Subsequently, according to the calculated second dosage, the tin-containing precursor solution was added to the halofatty acid dispersant solution and thoroughly mixed to form a more stable dispersion system between tin ions and dispersant molecules, resulting in a secondary impregnation solution. Then, using an equal-volume impregnation method, the secondary impregnation solution was loaded onto the surface and internal pores of the catalyst precursor, allowing the tin component and halofatty acid dispersant to simultaneously enter the support structure and form a more uniform spatial distribution with the already loaded platinum component within the pores. The carboxyl groups in the halofatty acid dispersant can interact with the metal precursor, while the halogen substituents can regulate the electronic environment surrounding the metal component, thereby improving the dispersion uniformity of the tin component and subsequent Pt-Sn active centers, and reducing the probability of metal particle migration and growth during calcination.

[0049] After impregnation, the sample is dried at 90-120℃ for 12-36 hours to allow the solvent to gradually evaporate and promote the stable adhesion of the tin precursor and dispersant to the surface and pore structure of the support. Subsequently, it is calcined at 500-650℃ for 1-4 hours to decompose and transform tin chloride, simultaneously fixing the dispersion modification within the active component system, ultimately yielding a Pt-Sn bimetallic modified catalyst semi-finished product. This step not only achieves the effective introduction of the tin component but also significantly improves the dispersion stability of the active component using a halofatty acid dispersant, allowing the platinum and tin components to be more uniformly distributed on the surface and within the pores of the composite support. This effectively inhibits the aggregation of the active component and reduces the tendency for deep cracking side reactions during the reaction process.

[0050] The catalyst semi-finished product was reduced under a hydrogen atmosphere to obtain the cycloalkyl oil hydroisomerization catalyst.

[0051] Specifically, after the tin component and halo-fatty acid dispersant are loaded and calcined, the platinum and tin components in the catalyst still mainly exist in the oxidized state or precursor-derived state. At this time, a metal active center with high catalytic activity has not yet been formed, so a reduction treatment is required to activate the catalyst performance.

[0052] The calcined catalyst semi-finished product was placed in a tubular reduction furnace and reduced under continuous high-purity hydrogen gas. Hydrogen not only acted as a reducing agent but also maintained a stable reducing atmosphere throughout the reduction process, preventing the active components from being re-oxidized. During isothermal reduction at 450-500℃ for 1-3 hours, platinum oxide was gradually reduced to metallic platinum by hydrogen, forming active centers with excellent hydrotreating and dehydrogenation capabilities. Simultaneously, the tin component also underwent corresponding reduction and structural transformation, gradually forming a more stable synergistic system with the platinum component. Since the halogenated fatty acid dispersant in the preceding steps had already promoted the uniform dispersion of the metal components on the support surface and within the pores, it effectively suppressed metal particle migration and sintering during the reduction process, ensuring that the formed platinum active centers maintained high dispersion and a large active surface area. As the reduction process continued, a more stable bonding structure formed between the active components and the composite support, ultimately constructing a bifunctional catalytic system with both hydrotreating and dehydrogenation functions and isomerization capabilities. After reduction, the furnace is cooled to room temperature to avoid structural stress caused by sudden cooling of the active metal or re-oxidation caused by exposure to air at high temperature, thereby obtaining a structurally stable cycloalkyl oil hydroisomerization catalyst.

[0053] The present invention will be further illustrated by specific embodiments below, but the scope of protection of the present invention is not limited to the following embodiments. Unless otherwise specified, all raw materials are conventional commercial products in the art, and all test methods are conventional test methods in the art. All embodiments and comparative examples in this batch use a uniform composite carrier, which is prepared by compounding ZSM-22 and ZSM-48 at a mass ratio of 1:5. The raw material ratio, molding and calcination preparation process of the carrier are completely consistent to eliminate experimental interference caused by differences in carrier structure. The experiment only controls three variables: the loading of precious metal Pt, the addition of metal modification agent Sn, and the addition of halogenated fatty acid dispersant M. By preparing multiple catalysts with different components and carrying out hydroisomerization performance evaluation of cycloalkyl oil, the focus is on exploring the effects of Pt, Sn, and dispersant M individually and synergistically on the dispersion of the active metal component of the catalyst, the isomerization and pour point depressant effect of oil, and the yield of liquid products.

[0054] Example 1 The mass ratio of the cycloalkyl oil hydroisomerization catalyst is as follows: 5% ZSM-23 molecular sieve, 25% ZSM-48 molecular sieve, 70% γ-Al2O3, 3% guar gum powder, Pt loading 0.3%, Sn loading 1.8%, and M addition 1.0%.

[0055] Preparation method: The above-mentioned support powder was mixed evenly, kneaded and shaped with 2% dilute nitric acid solution, dried at 110 ℃ for 12 h, and calcined at 550 ℃ for 3 h to obtain the support; a 0.5 g / L chloroplatinic acid aqueous solution was prepared, and Pt was impregnated and loaded under negative pressure with equal volume, dried at 110 ℃ for 24 h, and calcined at 550 ℃ for 2 h; the water absorption rate of the catalyst was determined, and the total mass of the required solution was calculated; dispersant M was weighed according to the proportion, dissolved in a certain amount of water, and then 0.2 g / L tin chloride ethanol solution was added to make its mass equal to the total mass of the required solution, and Sn was impregnated and loaded under negative pressure for a second time, dried at 110 ℃ for 24 h, and calcined at 550 ℃ for 2 h; finally, it was reduced at 480 ℃ for 2 h in a hydrogen atmosphere to obtain the target catalyst.

[0056] The specific catalyst preparation steps in Examples 2-9 are the same as in Example 1, with only the specific amounts of substances added listed: Table 1. Catalyst composition parameters for different embodiments and comparative examples. Comparative Example 1 The traditional single Pt modified catalyst was used without Sn promoter, with the corresponding M content added. The support was a molecular sieve / γ-Al2O3 composite support with the same ratio. The rest of the preparation process was completely consistent with Example 1.

[0057] Comparative Example 2 The traditional single Pt modified catalyst was used without M dispersant, and the corresponding Sn content was added. The support was a molecular sieve / γ-Al2O3 composite support with the same ratio. The rest of the preparation process was completely consistent with Example 1.

[0058] Comparative Example 3 The traditional single Pt modified catalyst was used, without M dispersant or Sn promoter. The support was a molecular sieve / γ-Al2O3 composite support with the same ratio. The rest of the preparation process was completely consistent with Example 1.

[0059] The above catalyst was used in an evaluation experiment of the hydroisomerization of a certain cycloalkyl oil. The reaction conditions were: temperature 320℃, pressure 16.0 MPa, and volume hourly space velocity 0.7 h⁻¹. -1 With a hydrogen-to-oil ratio of 1000:1, the evaluation results are shown in the table below: Table 2 Performance evaluation results of catalysts in each embodiment and comparative example As can be seen from the data in Table 2, compared with the other pairs, the catalyst prepared by simultaneously introducing Pt, Sn and metal M has significantly improved metal dispersion performance and oil pour point depressing performance. Examples 1, 2, and 3 all introduced Sn as an additive, increasing the dispersion of active metals in the catalyst to 46.8%–53.7%, significantly higher than comparative examples 1 and 3 without Sn. Higher metal dispersion means more effective active sites available to the catalyst, a greater reduction in the pour point of the oil, and a simultaneous increase in liquid product yield, confirming that the Sn additive can effectively disperse and anchor the active Pt component.

[0060] Comparing the results of Example 4 and Comparative Example 2, it can be seen that the introduction of halogenated fatty acids can further optimize the dispersion state of the active components and improve the dewaxing performance of the catalyst.

[0061] The catalyst prepared using the formulation in Example 4 exhibits the best overall performance, with the lowest oil pour point and the highest yield of liquid products.

[0062] To further clarify the technical effects of the embodiments of the present invention, please refer to [link / reference]. Figure 2 ,Depend on Figure 2It can be seen that the metal dispersion of Examples 1-7 were 40.8%, 42.3%, 49.7%, 53.7%, 46.8%, 47.5%, and 50.4%, respectively, which were generally higher than those of Comparative Examples 1-3 (39.6%, 36.5%, and 30.9%). Among them, Example 4 had the highest metal dispersion, reaching 53.7%, which was 14.1, 17.2, and 22.8 percentage points higher than Comparative Examples 1, 2, and 3, respectively. This indicates that introducing Sn component into the Pt component and combining it with halogenated fatty acid dispersants can effectively improve the dispersion state of active metals on the surface and inside the pores of the composite carrier, reduce the local enrichment and agglomeration of active components, and improve the utilization of effective metal active sites, thereby providing a basis for a good synergistic effect between the metal active center and the acidic center of the composite carrier.

[0063] Please see Figure 3 The feedstock oil had a pour point of -15°C. After hydroisomerization treatment with the catalysts in Examples 1-7, the pour points of the resulting oils decreased to -48°C, -52°C, -56°C, -62°C, -51°C, -54°C, and -58°C, respectively, which were generally lower than -39°C, -46°C, and -42°C of Comparative Examples 1-3. Among them, Example 4 had the lowest pour point at -62°C, a decrease of 47°C compared to the feedstock oil, and a further decrease of 23°C, 16°C, and 20°C compared to Comparative Examples 1-3, respectively. The above results indicate that the present invention, through the synergistic effect of the pore structure and acidic centers provided by the composite support and the Pt-Sn bimetallic active centers, can effectively promote the conversion of n-chain long-chain alkanes to branched isoalkanes in cycloalkyl oils and inhibit unfavorable deep cracking reactions, thereby significantly reducing the pour point of the product and improving the low-temperature flow properties of cycloalkyl oils.

[0064] Please see Figure 4 The density of the crude oil is 881 kg / m³. 3 After treatment with the catalysts described in Examples 1-7, the resulting products had densities of 869.8 kg / m³. 3 870.2 kg / m 3 870.8 kg / m 3 871.4 kg / m 3 870.8 kg / m 3 870.6 kg / m 3 and 869.7 kg / m 3 The overall value remained stable at 869.7–871.4 kg / m³. 3 Within a narrower range, compared to 870.1 kg / m³ in Comparative Examples 1–3. 3 868.3 kg / m 3 and 867.6 kg / m 3 They are at similar magnitudes. (Combined) Figure 3The significant pour point reduction effect shown indicates that this invention lowers the product pour point without causing a substantial decrease in product density. This suggests that it does not primarily achieve pour point reduction through extensive cracking to generate low-density, light components, but rather by promoting skeletal isomerization of hydrocarbon molecules to regulate product properties. Therefore, this result indirectly demonstrates that this invention can suppress excessive cracking while achieving isomerization pour point reduction, which is beneficial for maintaining the stability of the main liquid product composition.

[0065] Please see Figure 5 The liquid yields of Examples 1-7 were 93.2%, 97.9%, 98.5%, 99.7%, 97.5%, 97.2%, and 95.5%, respectively, with Examples 2-6 all exceeding 97%, and Example 4 reaching the highest at 99.7%. In contrast, the liquid yields of Comparative Examples 1-3 were 95.6%, 92.7%, and 94.3%, respectively. These results indicate that the cycloalkyl oil hydroisomerization catalyst provided in this invention can effectively reduce liquid product loss due to deep cracking during hydroisomerization and improve the retention of the target liquid product. In particular, Example 4 achieved a liquid yield of 99.7% while maintaining a metal dispersion of 53.7% and a product pour point reduced to -62°C. This demonstrates that this invention can maintain a high liquid product yield while significantly improving the pour point reduction effect, achieving reasonable control between the isomerization and cracking reactions, thus balancing high dispersion of active components, low product pour point, and high liquid yield, exhibiting good overall hydroisomerization performance.

[0066] In summary, the cycloalkyl oil hydroisomerization catalyst and its preparation method provided in this embodiment of the invention utilize a composite support made of molecular sieves, inorganic oxide binders, and molding aids. This provides a suitable acidic reaction environment and a stable support structure for the hydroisomerization reaction. The active component system includes platinum and tin. The platinum component provides hydrogenation / dehydrogenation active centers, promoting the isomerization reaction of n-alkanes. The tin component modifies the platinum component, which is beneficial to improving the dispersion stability of the active component. At the same time, the active component system is formed by dispersion modification with halogenated fatty acid dispersants, enabling the active component to be more uniformly distributed on the surface and inside the pores of the composite support, reducing the probability of migration and aggregation of the active component. Through the synergistic effect of the composite support, platinum component, tin component, and halogenated fatty acid dispersant, the dispersion stability of the active component is improved while effectively regulating the balance between isomerization and cracking reactions. This promotes the conversion of raw materials to target isomeric alkanes and inhibits deep cracking side reactions, thereby improving isomerization selectivity and liquid product yield. This solves the problem in the existing technology where cycloalkyl oil hydroisomerization catalysts are prone to active component agglomeration and cracking side reactions, making it difficult to achieve both isomerization selectivity and liquid product yield.

[0067] It should be clarified that the present invention is not limited to the specific configurations and processes described above and shown in the figures. For the sake of brevity, detailed descriptions of known methods are omitted here. In the above embodiments, several specific steps are described and shown as examples. However, the method process of the present invention is not limited to the specific steps described and shown. Those skilled in the art can make various changes, modifications, and additions, or change the order of steps, after understanding the spirit of the present invention.

[0068] It should also be noted that the exemplary embodiments mentioned in this invention describe methods or systems based on a series of steps or apparatus. However, this invention is not limited to the order of the steps described above; that is, the steps can be performed in the order mentioned in the embodiments, or in a different order, or several steps can be performed simultaneously.

[0069] The above description is merely a specific embodiment of the present invention. Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the specific working processes of the systems, modules, and units described above can be referred to the corresponding processes in the foregoing method embodiments, and will not be repeated here. It should be understood that the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.

Claims

1. A catalyst for the hydroisomerization reaction of cycloalkyl oils, characterized in that, It includes a composite carrier and an active component system loaded on the composite carrier; The composite carrier is prepared by mixing, molding and calcining composite carrier raw materials, which include molecular sieves, inorganic oxide binders and molding aids. The active component system is a Pt-Sn bimetallic composite system, which includes a noble metal component and a metal-modifying agent, and the active component system is formed by dispersion modification with a halogenated fatty acid dispersant.

2. The cycloalkyl oil hydroisomerization catalyst according to claim 1, characterized in that, The molecular sieve includes two of ZSM-23, ZSM-48 and ZSM-22, and the molecular sieve accounts for 20-80% of the total mass of the composite carrier raw material.

3. The cycloalkyl oil hydroisomerization catalyst according to claim 1, characterized in that, The inorganic oxide binder includes γ-alumina, which accounts for 10-30% of the total mass of the composite carrier raw materials.

4. The cycloalkyl oil hydroisomerization catalyst according to claim 1, characterized in that, The molding aid includes guar gum powder, which accounts for 2-5% of the total mass of the composite carrier raw materials.

5. The cycloalkyl oil hydroisomerization catalyst according to claim 1, characterized in that, The platinum comprises 0.3-1% of the total mass of the catalyst.

6. The cycloalkyl oil hydroisomerization catalyst according to claim 1, characterized in that, The tin comprises 1.5-5% of the total mass of the catalyst.

7. The cycloalkyl oil hydroisomerization catalyst according to claim 1, characterized in that, The halogenated fatty acid dispersant includes monochloroacetic acid, dichloroacetic acid, monobromoacetic acid, and dibromoacetic acid; the halogenated fatty acid dispersant accounts for 0.5-2% of the total mass of the catalyst.

8. A method for preparing a catalyst for the hydroisomerization reaction of cycloalkyl oils, characterized in that, The method for preparing the cycloalkyl oil hydroisomerization catalyst as described in any one of claims 1-7 comprises: The molecular sieve, the inorganic oxide binder, and the molding aid are mixed evenly, and then an acidic solution of a preset concentration is added and kneaded to obtain a plastic mixture. The plastic mixture is extruded, dried, and calcined to obtain a composite carrier; The first amount of platinum-containing precursor impregnation solution is determined based on the water absorption rate of the composite carrier. According to the first dosage, the platinum-containing precursor impregnation liquid is loaded onto the composite support using a negative pressure equal volume impregnation method, and the loaded composite support is dried and calcined to obtain a platinum-loaded catalyst precursor. The second amount of the secondary impregnation solution is determined based on the water absorption rate of the catalyst precursor. According to the second dosage, the tin-containing precursor solution is mixed with the halo-fatty acid dispersant solution to obtain the secondary impregnation solution. The secondary impregnation solution is loaded onto the catalyst precursor by an equal-volume impregnation method, and the loaded catalyst precursor is dried and calcined to obtain the catalyst semi-finished product. The catalyst semi-finished product was reduced under a hydrogen atmosphere to obtain the cycloalkyl oil hydroisomerization catalyst.

9. The method for preparing the cycloalkyl oil hydroisomerization catalyst according to claim 8, characterized in that, The platinum-containing precursor impregnation solution is loaded onto the composite support using a negative pressure equal-volume impregnation method according to the first dosage, and the loaded composite support is dried and calcined to obtain a platinum-loaded catalyst precursor comprising: Chloroplatinic acid was dissolved in deionized water to prepare a platinum-containing precursor impregnation solution. The composite carrier is placed under negative pressure and vacuumed to remove the gas from the pores of the composite carrier. The platinum-containing precursor impregnation solution is introduced into the composite carrier according to the first dosage, so that the platinum-containing precursor impregnation solution enters the pores of the composite carrier under negative pressure and completes the equal volume impregnation. The impregnated composite carrier is dried at 90-120℃ for 12-36 hours. The dried composite support was calcined at 500-650℃ for 1-4 hours to obtain the catalyst precursor.

10. The method for preparing the cycloalkyl oil hydroisomerization catalyst according to claim 8, characterized in that, The second dosage involves mixing the tin-containing precursor solution with a halofatty acid dispersant solution to obtain the secondary impregnation solution. The secondary impregnation solution is then loaded onto the catalyst precursor using an equal-volume impregnation method. The loaded catalyst precursor is then dried and calcined to obtain a catalyst semi-finished product comprising: The halogenated fatty acid dispersant is dissolved in a solvent to obtain a halogenated fatty acid dispersant solution. Tin chloride was dissolved in ethanol to obtain a tin-containing precursor solution; The tin-containing precursor solution is added to the halo-fatty acid dispersant solution according to the second dosage and mixed to obtain the secondary impregnation solution; The secondary impregnation solution is loaded onto the surface and pores of the catalyst precursor using an equal-volume impregnation method, so that the tin component and the halogenated fatty acid dispersant are uniformly dispersed on the catalyst precursor. The impregnated catalyst precursor was dried at 90-120℃ for 12-36 hours. The dried catalyst precursor was calcined at 500-650℃ for 1-4 hours to obtain the catalyst semi-finished product.

Citation Information

Patent Citations

  • Treatment method for naphthenic oil

    CN110540873A

  • Base oil of transformer oil and preparation method thereof

    CN114806634A